Merrifield Resin-supported Functionalized Amino Acids as Efficient Catalysts for the Cycloaddition of Carbon Dioxide with Epoxides - Lee, Seon-Myung; Kim, Moon-Il; Kim, Dong-Woo; Roshan, Roshith; Park, Dae-Won (Current Green Chemistry, 2015)
Various amino acids were covalently grafted onto DVB cross-linked polystyrene resin (Merrifield resin, PS) and functionalized with alkyl halides of different alkyl chain lengths and counter-anions. The catalysts were characterized by elemental analysis (EA), FT-IR, TGA, XPS, and SEM. The catalysts exhibited good reactivity in the cycloaddition of alkyl glycidyl ether (AGE) and CO2. The effects of the alkyl-halide structure, reaction temperature and CO2 pressure on the reactivity of the catalysts were also investigated. The catalyst could be reused for up to three consecutive runs without a severe reduction in the initial activity.
Keywords: Amino acid